Principal Leadership Function on Teacher Performance for Secondary Schools - M. Said Saggaf; Denok Sunarsi; Hariyaty Ab Wahid; Dodi Ilham; Achmad Rozi (International Journal of Educational Administration, Management, and Leadership, 2021)
Education is a fundamental factor that determines the quality of the human development index in any country. Leadership plays an essential role in many organizations, including educational organizations. Principals determine how education fosters and how teachers improve and develop students. Several factors could influence how a principal leads and manages subordinates. The principal's leadership function covers many excellent leadership functions within the educational system, including the educational administrator, educational supervisor, and educational leader. This study employed a quantitative research approach. Forty teachers participated as respondents in this research. The results showed that teachers' performance in the teaching and learning process was in the category of "very good", with indicators of preparation of learning implementation plan, implementation of learning, and evaluation/assessment of learning. As predicted by some theories and empirical findings, a good leadership practice would positively impact organizations. Like other organizations, Schools are also influenced by their leaders and how leaders function within the school system. This study shows a significant influence of the principal's leadership function on teacher performance in the teaching and learning process at the secondary school of Makassar, South Sulawesi, Indonesia, with its influence in a stable category. Many studies had documented the link between leaders' performance and their subordinates' performance as the leaders showed an optimal function so their subordinates. This trend also occurred between principals and their teachers. Teachers would show an outstanding performance as a response to the positive principal leadership in the schools.